THE COMMODIFICATION OF ENGLISH IN BRAZILIAN PUBLIC UNIVERSITIES: LANGUAGE IDEOLOGIES ENTEXTUALIZED IN THE SCOPE OF THE PROGRAM ENGLISH WITHOUT BORDERS - Szundy, Paula Tatianne Carréra (Revista da Anpoll, 2016)
In line with the dialogues that Brazilian applied linguists have established with the fields of sociolinguistics of globalization (BLOMMAERT, 2010) and language ideologies (WOOLARD, 1998; KROSKRITY, 2004) this paper focuses on the language ideologies entextualized in the scope of the program English Without Borders. Parting from the assumption that language faculties in Brazilian public universities have become markets in which English stands as a strategic commodity for students’ mobility in the scope of internationalization policies, discourses about English as the lingua franca for transnational mobility become arenas in which ideologies related to mobility, globalization and nativeness are (re)signified. Taking the program Languages Without Borders and, within it, English Without Borders, as one of these markets, I look into pieces of institutional discourses about the program to problematize the monolingual native-based language ideology and the colonial view of globalization entextualized in these discourses. This work is licensed under a Creative Commons Attribution 3.0 License.